Strategi RRI PRO2 STRATEGY IN INCREASING MILENIAL LISTENERS IN THE CITY OF PALEMBANG - Dwi Nur Alim; Rina Pebriana (Jurnal Prodi Ilmu Komunikasi, 2022)
Nowadays, radio broadcast programs continue to strive to maintain their existence by trying several strategies to increase listeners, especially the millennial generation. However, young people today are starting to lose interest in listening to radio and are more interested in listening to music or looking for news using applications on smartphones such as YouTube, Instagram and other applications. LPP RRI Palembang as a forum for broadcasting information, news, and entertainment services for all levels of society throughout the South Sumatra region has 4 programs, including Pro 1 , Pro, 2, Pro 3, and Pro 4. LPP RRI Pro 2 is a broadcast center for young people's creativity which is also one of the radio broadcasters that has a strategy in increasing the existence of millennial listeners. The purpose of this study was to find out the strategy carried out by RRI Palembang in increasing the interest of millennial listeners in RRI PRO 2. This research method was descriptive qualitative, which was used to understand directly based on the facts how the RRI PRO 2 strategy in increasing the interest of millennial listeners in Palembang City. The results of this study show that there are various strategies used by RRI Palembang in increasing millennial listening interest in Palembang City towards Pro2 broadcasts, namely by broadcasting off air and on air, packaging interesting programs, and through streaming broadcasts on social media